Physical activity, alcohol consumption, BMI and smoking status before and after prostate cancer diagnosis in the ProtecT trial: Opportunities for lifestyle modification. Issue 6 (1st April 2015) - Hackshaw‐McGeagh, Lucy E.; Penfold, Chris M.; Walsh, Eleanor; Donovan, Jenny L.; Hamdy, Freddie C.; Neal, David E.; Jeffreys, Mona; Martin, Richard M.; Lane, J. Athene; the ProtecT Study Group
<x xml:space="preserve">Abstract</x> Associations between certain lifestyle characteristics and prostate cancer risk have been reported, and continuation post‐diagnosis can adversely affect prognosis. We explored whether men make spontaneous changes to their physical activity and alcohol intake, body mass index (BMI) and smoking status, following a diagnosis of localised prostate cancer. A detailed diet, health and lifestyle questionnaire was completed by 511 participants within the Prostate Testing for Cancer and Treatment (ProtecT) randomised controlled trial, both before and 9 months after a diagnosis of prostate cancer. Of 177 men who were insufficiently active before their diagnosis (median 0 activity units/week; IQR 0–9), 40.7% had increased their activity by a median of 22 U week−1 (IQR 15–35) 9 months later, and there was weak evidence that men were more active after diagnosis than before (p = 0.07). Men categorised as "working" occupational social class and who were insufficiently active before diagnosis were 2.03 (95%, CI = 1.03–3.99, p = 0.04) times more likely to have increased their physical activity levels compared to men classified as "managerial or professional." Similarly, men who were insufficiently active pre‐diagnosis and with T‐stage 2 compared with T‐stage 1 prostate cancer were 2.47 (95%, CI = 1.29–4.71, p = 0.006) times more likely to be sufficiently active post‐diagnosis. Following diagnosis, there was an overall reduction in alcohol intake (p = 0.03) and the proportion of current smokers (p = 0.09), but no overall change in BMI. We conclude that some men spontaneously change certain lifestyle behaviours on receiving a diagnosis of prostate cancer. For many men, however, additional support through lifestyle interventions is probably required to facilitate and maintain these changes.